The digital transformation of tourism: a study of tourist behaviour and preferences in the age of technology in Bangladesh - Md Istiaq Mohhamad Shuvo; Md Jamsedul Islam (Research in Hospitality Management)
The rapid development of technology has profoundly altered tourist behaviour and trends, yet there is a notable gap in understanding how these changes affect tourists in Bangladesh. Existing research focuses on developed markets, overlooking Bangladesh’s unique sociocultural and economic factors. Consequently, there is limited knowledge about how Bangladeshi tourists interact with digital platforms. This study explores the digital transformation of tourism in Bangladesh, identifying significant links between technology acceptance, social media usage and travel experiences. Results show a strong connection between the use of travel technology and reliance on social media for decisions, with comfort in technology correlating with satisfaction in personalised travel platforms. Social media facilitates trip planning and booking, with tourists showing increased trust in online tools. The study underscores the transformative potential of digital technology in reshaping the travel landscape, urging industry players to innovate to meet evolving consumer expectations through quantitative analysis by using structural equation modelling (SEM) to examine the relationships among the variables. Further research is essential to provide insights for policymakers and industry stakeholders in Bangladesh to understand how Bangladeshi tourists interact with digital platforms.